The involvement of microRNA in the pathogenesis of Richter syndrome - Katrien Van Roosbroeck; Recep Bayraktar; Steliana Calin; Johannes Bloehdorn; Mihnea Paul Dragomir; Keishi Okubo; Maria Teresa Sabrina Bertilaccio; Simonetta Zupo; M. James You; Gianluca Gaidano; Davide Rossi; Shih-Shih Chen; et al. (Haematologica, 2019)
Richter syndrome is the name given to the transformation of the most frequent type of leukemia, chronic lymphocytic leukemia, into an aggressive lymphoma. Patients with Richter syndrome have limited response to therapies and dismal survival. The underlying mechanisms of transformation are insufficiently understood and there is a major lack of knowledge regarding the roles of microRNA that have already proven to be causative for most cases of chronic lymphocytic leukemia. Here, by using four types of genomic platforms and independent sets of patients from three institutions, we identified microRNA involved in the transformation of chronic lymphocytic leukemia to Richter syndrome. The expression signature is composed of miR-21, miR-150, miR-146b and miR-181b, with confirmed targets significantly enriched in pathways involved in cancer, immunity and inflammation. In addition, we demonstrated that genomic alterations may account for microRNA deregulation in a subset of cases of Richter syndrome. Furthermore, network analysis showed that Richter transformation leads to a complete rearrangement, resulting in a highly connected microRNA network. Functionally, ectopic overexpression of miR-21 increased proliferation of malignant B cells in multiple assays, while miR-150 and miR-26a were downregulated in a chronic lymphocytic leukemia xenogeneic mouse transplantation model. Together, our results suggest that Richter transformation is associated with significant expression and genomic loci alterations of microRNA involved in both malignancy and immunity.